The Problem of Consideration Torsion Emergence in Beams - Hudz, Sergiy; Gasii, Grygorii; Pents, Volodymyr (International Journal of Engineering and Technology, 2018)
The calculation of the steel unrestrained and partially restrained roof beams with initial imperfections main stages is discussed. Restraining can be done by structures attached to the steel beams, namely, profiled flooring and discrete joints. On the basis of the new approach to the internal forces analysis and the geometric properties specification, the purpose was to find and describe the differences in the beam work as the part of roofing, which distinguishes it from the work conditions of the free supported beam. The features of the beam operation with the joint flexural and torsion are singled out. The need to improve the existing theoretical model for present deficiencies elimination is indicated. The bearing capacity determining methods for the flexible elements stability exposed to bending and bending with torsion are compared. Their advantages and disadvantages are revealed. It is proposed to increase the material saving by applying calculations. At the end of the article, conclusions regarding the consideration of investigated factors are given.Â Â